The Influence of Training Programs and Motivation on Employee Work Productivity - Agatha Rinta Suhardi; Sari Dewi Oktari; Andi Budiawan (GoAcademica Research & Publishing, 2023)
Good employee work productivity is inseparable from the training programs provided by the company where the employee works. In practice, more emphasis is placed on training programs to make employees more enthusiastic, so that employee work productivity can increase according to the targets set by the company. Another factor that can affect employee work productivity is the motivation of employees in the company. Motivation is a tool that can influence a person or group of people in an organization or institution to achieve the goals in it. The purpose of this study was to determine the effect of the Training and Motivation Program on Employee Productivity. Data processing was carried out by analyzing the correlation coefficient, the coefficient of determination, and testing the hypothesis. Based on the results of data processing, it was obtained that it simultaneously indicated that there was a significant influence of training programs and motivation on employee work productivity. Partially, the results of the study show that training programs have an effect on employee performance and motivation has an effect on employee productivity.